2015
DOI: 10.1016/j.rboe.2015.06.009
|View full text |Cite
|
Sign up to set email alerts
|

Partial rotator cuff injury in athletes: bursal or articular?

Abstract: A painful shoulder is a very common complaint among athletes, especially in the case of those in sports involving throwing. Partial lesions of the rotator cuff may be very painful and cause significant functional limitation to athletes’ sports practice. The incidence of partial lesions of the cuff is variable (13–37%). It is difficult to make the clinical and radiological diagnosis, and this condition should be borne in mind in the cases of all athletes who present symptoms of rotator cuff syndrome, including … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
8
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 53 publications
0
8
0
1
Order By: Relevance
“…Articular-sided tears are more common than bursal-sided tears. A study on athletes showed a similar trend, but noted a higher number of articular-sided tears in athletes who throw repeatedly, while bursal-sided tears were likely in weightlifters [26]. Differences in the composition of these two regions (complex of tendon, joint, and ligament in articular-sided v. tendon bundles in bursal-sided regions) may be a reason why articular-sided regions are more vulnerable to a tensile load [27].…”
mentioning
confidence: 89%
“…Articular-sided tears are more common than bursal-sided tears. A study on athletes showed a similar trend, but noted a higher number of articular-sided tears in athletes who throw repeatedly, while bursal-sided tears were likely in weightlifters [26]. Differences in the composition of these two regions (complex of tendon, joint, and ligament in articular-sided v. tendon bundles in bursal-sided regions) may be a reason why articular-sided regions are more vulnerable to a tensile load [27].…”
mentioning
confidence: 89%
“…Regarding the etiology of partial tears, bursal-side tears tend to be primarily caused by biomechanical subacromial impingement on a progressively degenerated tendon, while articular side tears result from trauma, repetitive movements, and/or an insidious start associated with degenerative age-related alterations on the tendon. In contrast, intrasubstance tears can result from internal tendon degeneration, namely cellular or extracellular matrix degenerative degradation [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“… 12 Partial rotator cuff injuries has an incidence of 13% to 37% of world population. 13 However, rotator cuff surgical repair, either open or arthroscopic, is the best conduct in case of persistent pain and evolutive muscle weakness. 14 Peripheral nerve block may provide adequate analgesia in immediate postoperative until 20 hours.…”
Section: Introductionmentioning
confidence: 99%